Is Grit Associated with Burnout and Well-being in Orthopaedic Resident and Faculty Physicians? A Multi-institution Longitudinal Study Across Training Levels. Issue 12 (29th December 2021) - Lee, Donald H.; Reasoner, Kaitlyn; Lee, Diane; Davidson, Claudia; Pennings, Jacquelyn S.; Blazar, Philip E.; Frick, Steven L.; Kelly, Anne M.; LaPorte, Dawn M.; Lese, Andrea B.; Mercer, Deana M.; Ring, David; et al.
Abstract: Background: Grit has been defined as "perseverance and passion for long-term goals" and is characterized by maintaining focus and motivation toward a challenging ambition despite setbacks. There are limited data on the impact of grit on burnout and psychologic well-being in orthopaedic surgery, as well as on which factors may be associated with these variables. Questions/purposes: (1) Is grit inversely correlated with burnout in orthopaedic resident and faculty physicians? (2) Is grit positively correlated with psychologic well-being in orthopaedic resident and faculty physicians? (3) Which demographic characteristics are associated with grit in orthopaedic resident and faculty physicians? (4) Which demographic characteristics are associated with burnout and psychologic well-being in orthopaedic resident and faculty physicians? Methods: This study was an institutional review board–approved interim analysis from the first year of a 5-year longitudinal study of grit, burnout, and psychologic well-being in order to assess baseline relationships between these variables before analyzing how they may change over time. Orthopaedic residents, fellows, and faculty from 14 academic medical centers were enrolled, and 30% (335 of 1129) responded. We analyzed for the potential of response bias and found no important differences between sites in low versus high response rates, nor between early and late responders. Participants completed an email-based survey consisting of the Duckworth Short Grit Scale, Maslach Burnout Inventory-Human Services (Medical Personnel) Survey, and Dupuy Psychological Well-being Index. The Short Grit Scale has been validated with regard to internal consistency, consensual and predictive validity, and test-retest stability. The Psychological Well-being Index has similarly been validated with regard to reliability, test-retest stability, and internal consistency, and the Maslach Burnout Inventory has been validated with regard to internal consistency, reliability, test-retest stability, and convergent validity. The survey also obtained basic demographic information such as survey participants' age, gender, race, ethnicity, marital status, current year of training or year in practice (as applicable), and region of practice. The studied population consisted of 166 faculty, 150 residents, and 19 fellows. Beyond the expected age differences between sub-populations, the fellow population had a higher proportion of women than the faculty and resident populations did. Pearson correlations and standardized β coefficients were used to assess the relationships of grit, burnout, psychologic well-being, and continuous participant characteristics. Results: We found moderate, negative relationships between grit and emotional exhaustion (r = -0.30; 95% CI -0.38 to -0.21; p < 0.001), depersonalization (r = -0.34; 95% CI -0.44 to -0.23; p < 0.001), and the overall burnout score (r = -0.39; 95% CI -0.48 to -0.31; p < 0.001). The results also showed a positive correlation between grit and personal accomplishment (r = 0.39; 95% CI 0.29 to 0.48; p < 0.001). We also found a moderate, positive relationship between grit and psychologic well-being (r = 0.39; 95% CI 0.30 to 0.49; p < 0.001). Orthopaedic surgeons with 21 years or more of practice had higher grit scores than physicians with 10 to 20 years of practice. Orthopaedic surgeons in practice for 21 years or more also had lower burnout scores than those in practice for 10 to 20 years. Married physicians had higher psychologic well-being than unmarried physicians did. Conclusion: Among orthopaedic residents, fellows, and faculty, grit is inversely related to burnout, with lower scores for emotional exhaustion and depersonalization and higher scores for personal accomplishment as grit increases. Clinical Relevance: The results suggest that grit could be targeted as an intervention for reducing burnout and promoting psychologic well-being among orthopaedic surgeons. Other research has suggested that grit is influenced by internal characteristics, life experiences, and the external environment, suggesting that there is potential to increase one's grit. Residency programs and faculty development initiatives might consider measuring grit to assess for the risk of burnout, as well as offering curricula or training to promote this psychologic characteristic.